Assessing Global Warming, Acidification, and Eutrophication Impacts of Pempek Production Using Life Cycle Assessment: A Case Study in Palembang, Indonesia - Bayu Wahyudi; Anindita Rahmalia Putri; Yasmin Yasmin; Nadia Eka Damayanti; Tiara Wijaya (Agroindustrial Technology Journal, 2026)
Traditional food production may generate environmental burdens through raw material sourcing, energy consumption, processing activities, packaging, distribution, and waste generation. This study assessed the environmental impacts of pempek production in a small-scale industry in Palembang, Indonesia, using the Life Cycle Assessment (LCA) approach. The assessment was conducted using the CML-IA Baseline method in SimaPro version 9.5.0.0, with a system boundary covering raw material procurement, dough preparation, resting, shaping, frying, packaging, distribution, and waste-related activities. Inventory data were collected based on one production cycle at Pempek X and included material inputs, energy use, water use, fuel consumption, packaging materials, and emission factors. The results showed that pempek production generated 311.96 kg CO₂-eq for Global Warming Potential (GWP), 2.397 kg SO₂-eq for Acidification Potential (AP), and 4.197 kg PO₄³⁻-eq for Eutrophication Potential (EP) per production cycle. The frying stage was the main contributor to GWP (32.1%) and EP (61.3%), mainly due to thermal energy use and cooking oil consumption. The packaging stage contributed the largest share to AP (approximately 27.0%) and also had a substantial contribution to GWP (25.2%). From the raw material perspective, wheat flour was the dominant contributor across several impact categories, followed by palm oil, demersal fish, tofu, and eggs. These impacts were mainly associated with upstream agricultural activities, energy use, and material production processes. The findings indicate that energy-intensive processing, raw material supply chains, and packaging materials are key environmental hotspots in pempek production. Improving frying efficiency, selecting lower-impact packaging, strengthening waste management, and sourcing more sustainable raw materials were recommended to reduce environmental burdens. This study demonstrates the usefulness of LCA for identifying improvement priorities in traditional food production systems.